School Based Teacher Preparation : Possibilities and Challenges - S, Indumathi.; Sood, Sameera (Voices of Teachers and Teacher Educators, 2018)
This article discusses the school-based teacher preparation model run by a not-for profit organisation called I Am A Teacher (IAAT), Gurgaon. This is a one-year Post-Graduate Diploma in Learning and Teaching (PGDLT) programme. This course prepares teachers through a model where Student-Teachers spend minimum three days practicing in a host-school. This article describes the mentoring model and highlights how teachers are prepared through a blend of theory and practice. The voices of the Student- Teachers are presented through reflections and narration of their learning experiences. It briefly highlights the challenges of such a schoolbased model.